Penatalaksanaan Fisoterapi pada Kasus Eating Disorderdi Klinik Asya Center Jombang : Studi Kasus - Siti Nur Rahimatus Shifa; Atika Yulianti; Putri Sukma Rahayu (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Introduction: ED (Eating Disorders) is one of the most difficult mental disorders to treat and treat, and the cost is even higher than schizophrenia. Secondary somatic complications due to malnutrition, severe weight loss and low levels of micronutrients. Objective: To determine the effectiveness of a combination of interventions such as Expression Head Massage, Myofacial Release, Neurosenso Komplit, General Massage, Patterning, Play Therapy, Brain Gym, Oral Reflex Stimulation. Method: A single-subject study was conducted on a 22-month-old child with ED. Results: The results of the sensory examination evaluation showed an increase in sensory in the child. Conclusion: A 22-month-old child was diagnosed with Eating Disorder, initially given physiotherapy, the child did not want to eat rice at all, only wanted to drink milk and sometimes the child liked to hit and bite, but after doing routine physiotherapy and home programs, now the child is willing to feed 15 mouthfuls of rice and focus on the child has also begun to exist and the child's balance is increasing.